2023
DOI: 10.7759/cureus.34713
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Neural Epidermal Growth Factor-Like 1 Protein (NELL-1) Antigen-Associated Membranous Nephropathy

Abstract: Membranous nephropathy (MN) is an autoimmune disease resulting in nephrotic syndrome. Neural epidermal growth factor-like 1 protein (NELL-1) has been shown to cause a rare form of MN that is more likely to be associated with malignancy. We present a case of a 73-year-old female who was found to have a NELL-1-associated segmental MN. She presented complaining of generalized weakness, chills, and poor appetite, worsening over a one-week duration. Her kidney functions were noted to be markedly deranged, with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In 2019, a study of 210 PLA2R-negative MN biopsies found 16% positivity for NELL-1. This exceeded twice the number of THSD7A-positive cases (15 out of 154 PLA2R-negative cases, 10%) [ 9 ]. In 2021, Caza et al [ 10 ] found that 3.8% of MN cases negative for THSD7A and PLA2R were NELL-1 positive.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, a study of 210 PLA2R-negative MN biopsies found 16% positivity for NELL-1. This exceeded twice the number of THSD7A-positive cases (15 out of 154 PLA2R-negative cases, 10%) [ 9 ]. In 2021, Caza et al [ 10 ] found that 3.8% of MN cases negative for THSD7A and PLA2R were NELL-1 positive.…”
Section: Discussionmentioning
confidence: 99%